Use of N-methylene phosphonic chitosan to obtain an isoniazid prodrug (Revista Brasileira de Ciências Farmacêuticas, 2004)
Tuberculosis(TB) is one of the most neglected health problems and has been out of control in many areas of the world. Since new antituberculous alternatives, including controlled classical drug delivery systems, are urgently needed to face this serious situation, the purpose of the present work was the synthesis and characterization of a prolonged action prodrug of isoniazid. The N-methylene phosphonic chitosan (NMPC), a hydrosoluble derivative of chitosan was used as drug carrier. This analog, as well as its precursor, exhibits stimulatory activity on macrophages, host cells of Mycobacterium tuberculosis. Due to its hydrosolubility, it can be easily handled and intravenously administrated. The NMPC can be obtained by reaction of chitosan with phosphorous acid in presence of formaldehyde. Once synthesized, the coupling with isoniazid was carried out after two steps: functionalization of the drug with a succinic spacer group and activation of the succinyl isoniazid through the cyclic analog 1-(pyridine-4-carbonyl)-tetrahydro-pirydazin-3,6-dione.